Kualiti air di Sungai Kesit Batang Lemanak, Engkilili, Sarawak - Hasanaliza, Binti Bujang Abdillah. (Universiti Malaysia Sarawak (UNIMAS), 2005)
The main objectives of this study are to record and determine the water quality at Sungai Kesit and to classify Sungai Kesit based on Interim National Water Quality Standard ofMalaysia (INWQS). Sungai Kesit is one ofthe tributaries ofBatang Lemanak and the only tributary that is still not polluted due to the logging activities. Water samplings were conducted twice, once during dry season and once during rainy season. Five stations were chosen along Sungai Kesit and one station at Lubok Subong, Batang Lemanak. Six parameters chosen are dissolved oxygen (DO), biochemical oxygen demand (BOD5), chemical oxygen demand (COD), total suspended solid (TSS), ammonia-nitrogen and pH. Several other parameters that were measured are temperature, water transparency, conductivity, redox. river discharge, particles size analysis (PSA), reactive phosphorus and nitrate-nitrogen. The Water Quality Index (WQI) for Sungai Kesit and Batang Lemanak are 95.51 and 99.69 respectively during dry season while 98.80 and 93.36 respectively during rainy season which can be categorised as clean. Based on the INWQS, Sungai Kesit is in Class I for all parameters except BODs while Batang Lemanak is in Class I only for parameter such as COD. DO. pH and ammonia-nitrogen. Sungai Kesit is still clean and it can be categorize in Class I based on INWQS.